The Implementation of Net Games in Physical Education Learning in Elementary Schools: A Systematic Review - Mochamad Fikri Rachmadi; Suherman Slamet; Gano Sumarno; Wildan Alfia Nugroho (TEGAR: Journal of Teaching Physical Education in Elementary School, 2022)
According to previous research, problems are still found in the net game implementation. The problems are related to infrastructure and the absence of innovation in learning methods. The purpose of this study was to determine the implementation of net games and provide recommendations on how to implement the net games in Physical Education subject in elementary schools. The results of previous research on net games became the background for conducting the research using a systematic review method. The database for data search included Google Scholar, Taylor Francis, DOAJ, and Research Gate. From the four databases, 146 research on net games were found. For the systematic review stage, 20 studies were determined as the main sources of this study. From the 20 studies, findings to help solve problems occurring during the implementation of net games were found. The findings found from a table tennis game involved a happy bouncing ball, tennis bet modification, training methods, mini-pong, gender-based cooperative learning, audio-visual learning, Moodle courses, bet holding techniques, reciprocal teaching styles, and command learning styles. The findings found from the volleyball game included mini volleyball ball modification, 3 on 3 games, role-playing, libas game, faith-based methods in Islamic schools, Cooperative Learning Model, Tactical-Game, cooperative learning, Student Team Achievement Divisions (STAD), and a playful approach in volleyball games. Based on the 20 studies, the upper-grade elementary school students could participate in net games well. When problems occurred, they could use the findings that have been described.